Direct and indirect estimates of maternal mortality in rural Burkina Faso - Garenne, Michel; Sauerborn, Rainer; Nougtara, Adrien; Borchert, Matthias; Benzler, Justus; Diesfeld, Hans J. (Studies in family planning, 1997)
A retrospective study of maternal mortality was conducted in Nouna, a rural area of Burkina Faso in 1992. Strong evidence was found of a major mortality decline among children and young adults over the 50 years preceding the study: The estimated life expectancy of 36 years in around 1945 rose to 58 years in 1991. Direct and indirect (using the sisterhood method) estimates of the maternal mortality ratio (MMR) were compared. Overall, the direct estimate of the MMR (389 deaths per 100,000 live births) for women aged 15 and older was slightly lower than the indirect estimate (428 deaths per 100,000). Taking into account the biases involved in the use of information obtained from sisters, the direct estimates indicated a marked decline in maternal mortality over time from 569 deaths per 100,000 around 1941 to 305 deaths around 1987. The validity of both data and approach, as well as the discrepancies between the direct and indirect methods, are discussed. (STUDIES IN FAMILY PLANNING 1997; 28, 1: 54-61)
Gesehen am 23.10.2024